2019
DOI: 10.2147/ijgm.s223882
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identifying Key Challenges Facing Healthcare Systems In Africa And Potential Solutions</p>

Abstract: IntroductionHealthcare systems in Africa suffer from neglect and underfunding, leading to severe challenges across the six World Health Organization (WHO) pillars of healthcare delivery. We conducted this study to identify the principal challenges in the health sector in Africa and their solutions for evidence-based decisions, policy development and program prioritization.MethodsThe study was conducted as part of a recent African Epidemiological Association Meeting in Maputo, Mozambique with participants drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
221
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(294 citation statements)
references
References 18 publications
4
221
0
Order By: Relevance
“…More so, the trends of the COVID-19 fatality growth rates for Nigeria were relatively higher compared to the Global fatality growth rates from the (tdr2) all through the (trd8) periods covered in the study. contemporary studies addressing the state of the primary and community health in Nigeria revealed that the healthcare delivery system in the country was not only poor but also inadequate (4,6,12). Hence, the comparatively higher growth of COVID-19 fatalities in Nigeria could be attributed to the shortage of welltrained medical personnel and the ill-equipped of the few medical healthcare facilities in the country (7).…”
Section: Discussionmentioning
confidence: 99%
“…More so, the trends of the COVID-19 fatality growth rates for Nigeria were relatively higher compared to the Global fatality growth rates from the (tdr2) all through the (trd8) periods covered in the study. contemporary studies addressing the state of the primary and community health in Nigeria revealed that the healthcare delivery system in the country was not only poor but also inadequate (4,6,12). Hence, the comparatively higher growth of COVID-19 fatalities in Nigeria could be attributed to the shortage of welltrained medical personnel and the ill-equipped of the few medical healthcare facilities in the country (7).…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-pocket (OOP) spending is the main mode of healthcare financing in Nigeria -another implication of poor investment in healthcare by the government. 11 Even if a robotic surgical program is currently been implemented in the nation, OOP payment poses a major limitation to accessing such expensive surgical service. Aside from the huge initial cost of acquisition of the robot, an additional $700 to $3,500 for instruments and accessories per procedure puts the cost associated with robotic-assisted procedures in the range of $3,000 to $5,000.…”
Section: Current Challengesmentioning
confidence: 99%
“…9 Already, almost 70% of total healthcare financing is OOP, the most regressive method of healthcare financing, with resultant catastrophic health spending pushing many families into poverty. 11,13 Therefore, the high bill of robotic procedures cannot be afforded by many patients and their relatives.…”
Section: Current Challengesmentioning
confidence: 99%
“…Despite a high disease burden in most African countries, the provision of healthcare services is largely inadequate and ineffective. Possible reasons include challenges related to leadership and governance, health workforce, medical products, technologies, financing, and services delivery [4]. The shortage of health care workers in particular is a major cause for concern among other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Strong leadership style is probably the reason why nurses in Nigeria are more satisfied with their jobs when compared with their colleagues in other countries even though they may work for longer hours or earn relatively less salaries [6]. Moreover, factors related to the work environment, low payment, poor working conditions, limited educational and career opportunities, unsafe workplaces, and a lack of resources for effective working were reported from different parts of the world [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%